(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the integrative approach as a powerful pedagogical means of developing students’ creative activity. Modern education faces the urgent challenge of preparing individuals who are not only knowledgeable but also capable of generating new ideas, solving complex problems, and adapting to rapidly changing environments. The integrative approach, which combines knowledge, skills, and experiences from different disciplines into a unified educational process, provides fertile ground for fostering creativity. By linking theory with practice, science with art, and cognitive learning with emotional development, integration enriches students’ intellectual capacity and encourages divergent thinking.